Efficient Signalling with Dividends, Investment, and Stock Repurchases - WILLIAMS, JOSEPH (Journal of Finance, 1988)
ABSTRACT The efficient mix of dissipative dividends, investments in real and financial assets, and repurchases of stock is computed for a continuum of firms with inside information about the return on risky real assets. In the efficient signalling equilibrium, the representative firm optimally distributes dividends, invests in risky real assets to maximize net present value, holds no financial securities, and sells new stock in the market. This firm finances its value‐maximizing investment first from internal funds and second from stock sold to new investors.